UUD 1945 Sebagai Konstitusi Normatif (Pembatasan Masa Jabatan Presiden dan Wakil Presiden) - Leonard Umbu Saingu Ferdinandus (Fakultas Hukum Universitas Islam Syekh Yusuf, 2023)
This paper will identify (or diagnose) the problem of extending the term of office of the president and vice president in the normative constitutional concept. To overcome this problem, this article argues that we need to be a nation that is more obedient to the constitution, which restrictively stipulates that the President and Vice President only hold office for five years and can be re-elected for one more term. Based on these provisions, it should be noted that the constitution of the Constitution is a normative constitution which then gave birth to teachings or ideas of limited power in casu restrictions on the powers of the president and/or vice president. Keywords: Constitutionalism, Term of Office.